Application of ossein-hydroxyapatite complex for osteoporosis and fracture treatment (literature review) - Korzh, Mykola; Dedukh, Ninel (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2016)
Based on scientific information and the results of our studies suggest the influence of ossein-hydroхyapatite complex in treating patients with osteoporosis, fractures, and pseudarthrosis after arthroplasty. The drug contains growth factors (insulin-like growth factor-1 and 2, transforming growth factor-beta), which stimulates the proliferation and differentiation preosteogenic forming cells and regenerate specific tissue structures. Osteocalcin and collagen type I as components of ossein regulate osteoblast activity and bone remodeling and is the basis for the formation of matrix and for its mineralization. Mineral component of the drug, hydroxyapatite, contains calcium and phosphorus (2:1), and promotes osteoid mineralization, a full-fledged bone regenerate formation, maintaining the stability of bone matrix. As a result of experimental and clinical studies conducted in Ukraine and abroad, effectiveness of ossein-hydroxyapatite complex in patients with primary and secondary osteoporosis is proved. It is proved its positive impact for pain reducing in patients with degenerative diseases of the spine and knee joint arthritis. Established optimization impact of ossein-hydroxyapatite complex at all stages of reparative osteogenesis in various clinical situations of fracture regeneration, as well as in osteosynthesis. It was successfully used in patients with delayed union of long bone fractures. Presented evidence that the use of ossein-hydroxyapatite o complex helps to reduce the incidence of pseudarthrosis. The drug is effective in children with traumatic injuries and violation of long bones. Proven effectiveness of its use in the treatment of patients with osteopenia and osteoporosis after cementless-total hip arthroplasty.